ANALYSIS OF INDIVIDUAL AND ORGANIZATIONAL RESISTANCE TO CHANGE - Sri Wahyuni, Erika (SATUKATA: Jurnal Sains, Teknik, dan Studi Kemasyarakatan, 2022)
This study aims to narrate or inform the reader about change management. The type of research in this study is expanatory research with a quantitative approach. The research method used is the method of collecting data from various sources on the internet, by combining these sources into one. The data collection technique used is to find the required information. Change is commonplace at any time. Therefore, we need things that can regulate these changes to become more organized and achieve the goals of an organization or company. This is called Change Management. In change, there must be resistance, both individually and in groups within an organization or company. Change management is needed to overcome the resistance that occurs within the organization.